Performance of Management of the Red Pumpkin Beetle (Aulacophora foveicollis) Lucas on Bottle Gourd by Different Bio-Pesticides - Gahlot, Nandini; Kumar, Pradeep; Choudhary, A.K.; Gangwar, B.; Anisha (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A field experiment was conducted at Organic Research Farm, Karguaji, Bundelkhand University, Jhansi (U.P.) at Kharif season of 2023 to evaluate the bio-pesticide and botanicals effect to population reduction of red pumpkin beetle on bottle gourd crop, the experiment was carried out with 9 treatments including control in three replications under randomized block design. To evaluate efficacy three applications of treatments were carried out and data was collected at 3DAS, 7DAS and 14 days after spraying. After the observations at first second and third sprays the best effective treatment that reduced the maximum population of red pumpkin beetle was Beauveria bassiana @5gm/L followed by Neem oil @2ml/L and Bacillus thuringiensis @5gm/L, remain all botanicals and bio-pesticide found superior over control. The highest yield found with 442.21 qt/hac under Beauveria bassiana treated with plot followed by the 4.12.50qt/hac and 400.10qt/hac yield under Neem oil and Bt treated plots. The highest cost benefit ratio was found under Beauveria bassiana that showed 1:4.64 ratio followed by Bt and Metarrhizium anisopliae.